2008
DOI: 10.1007/s00018-008-7517-4
|View full text |Cite
|
Sign up to set email alerts
|

A conformationally isoformic thermophilic protein with high kinetic unfolding barriers

Abstract: The basis for the stability of thermophilic proteins is of fundamental interest for extremophile biology. We investigated the folding and unfolding processes of the homotetrameric Thermoanaerobacter brockii alcohol dehydrogenase (TBADH). TBADH subunits were 4.8 kcal/mol less stable towards guanidinium chloride (GdmCl) unfolding compared to urea, indicating ionic modulation of TBADH stability. Strongly denaturing conditions promoted mono-exponential unfolding kinetics with linear dependence on denaturant concen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
7
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 39 publications
0
7
0
Order By: Relevance
“…This leads to a slightly lower stability value for GdmCl compared to that for urea, despite the higher concentration of surfactant. Use of a stronger denaturant typically leads to higher extrapolated values of unfolding rates, though the reasons for this are not clear.…”
Section: Resultsmentioning
confidence: 99%
“…This leads to a slightly lower stability value for GdmCl compared to that for urea, despite the higher concentration of surfactant. Use of a stronger denaturant typically leads to higher extrapolated values of unfolding rates, though the reasons for this are not clear.…”
Section: Resultsmentioning
confidence: 99%
“…Structural flexibility of proteins from psychrophilic organisms result from low hydrophobicity in the protein core, low proline, and high glycine content (Hough and Dan-son1999;Feller 2003;Pica and Graziano 2016;Pucci and Rooman 2017). Thermophilic proteins, like Thermoanaerobacter brockii alcohol dehydrogenase (TBADH), show the involvement of additional salt bridges, hydrogen bonding, hydrophobicity, oligomerization, and strategically placed prolines to provide higher conformational stability than the mesophilic counterpart, Clostridium beijerinckii alcohol dehydrogenase (CBADH) (Bogin et al 1998;Mishra et al 2008). Similarly, acidophilic and alkaliphilic proteins show the preferences of acidic and basic amino acid residues respectively as their adaptive mechanism (Hough and Danson 1999;Reed et al 2013).…”
Section: Factors Responsible For Protein Stability In Extreme Environ...mentioning
confidence: 99%
“…Observing the intermediate structures contributes to our understanding of protein folding and unfolding. Biophysical techniques such as circular dichroism (CD), fluorescence spectroscopy, small-angle X-ray scattering, and nuclear magnetic resonance (NMR) spectroscopy allow us to monitor intermediate structures during conformational changes induced by thermal or chemical denaturation. Unfortunately, protein folding and unfolding are generally fast, and most intermediate structures are temporary and difficult to detect. Recent research in the field has indicated that some proteins from hyperthermophiles are stabilized by their remarkably slow unfolding rate. Therefore, we are able to detect the intermediates of these proteins because of their slow unfolding.…”
mentioning
confidence: 99%
“…Many hyperthermophilic proteins have considerable kinetic stability as measured by their high activation energy and slow unfolding kinetics. Well-studied examples are pyrrolidone carboxyl peptidase from the hyperthermophilic archaeon Pyrococcus furiosus (Pf-PCP) and ribonuclease H2 from the hyperthermophilic archaeon Thermococcus kodakarensis (Tk-RNase H2). The unfolding rate of Pf-PCP is 10 7 times slower than that of mesophilic PCP from Bacillus amyloliquefaciens .…”
mentioning
confidence: 99%